Theoretical Approaches to Multi-Cultural Positive Psychological Interventions 2019
DOI: 10.1007/978-3-030-20583-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Moving Forward in Fostering Humour: Towards Training Lighter Forms of Humour in Multicultural Contexts

Abstract: The following theoretical position paper has the aim to outline two important future directions of humour intervention research. Firstly, existing humour trainings have not differentiated explicitly between different uses of humour or humour that may be virtuous or not. Within the realm of Positive Psychology, all virtuous forms of humour need to be identified and interventions developed that aim at fostering these benevolent/lighter forms. Secondly, most humour trainings have been adapted and conducted in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Research has shown that humor interventions may be designed in various ways. 16–19 Humorous videos, 20 , 21 clown visits, 22–24 laughter yoga, 25 , 26 and other personalized interventions 27 have all shown benefit to some degree. Group and individual interventions 28 , 29 and the use of different kinds of humor 30–33 have been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that humor interventions may be designed in various ways. 16–19 Humorous videos, 20 , 21 clown visits, 22–24 laughter yoga, 25 , 26 and other personalized interventions 27 have all shown benefit to some degree. Group and individual interventions 28 , 29 and the use of different kinds of humor 30–33 have been tested.…”
Section: Introductionmentioning
confidence: 99%